“Factores de riesgo en el recien nacido de bajo peso de madres adolescentes Hospital de Apoyo “San José” Callao 1,995” - García Saavedra, Leydi (1996)
The pregnancy in the adolescent is a situation condition of high risk obstetric and perinatal. It is defined with the term of early primigesta to refer to those less than 19 ai'ios. (1) approximately 1'000, 000 pregnant women annually, instead ended in births, abortions. (1,2,3) teen which had 600,000 400,000 end up in there is evidence that the increased risk is more considerable in the case of women under 17 years, especially in those younger than 15 years. (4) when the family and the society support the teenager pregnant both antenatal care in childbirth and the newborn, the risk maternoperinatal is similar to the pregnant adult. And frankly less than the of the adolescent pregnant women not included in a comprehensive atencio1jt:b System. resolve (5.6). The most difficult are problems the social, economic and psychological. (7) 7 teenage pregnancy, i.e. between the fifteen years of age according to refie...